Indigenous endomycorrhizal fungi at salak (Salacca zalacca) plantations in Bali, Indonesia and their colonization of the roots - I Nyoman RAI; I Ketut Suada; Meitini Wahyuni Proborini; I Wayan Wiraatmaja; Mikhail SEMENOV; George Krasnov (Society for Indonesian Biodiversity, 2019)
Abstract. Rai IN, Suada IK, Proborini M, Wiraatmaja IW, Semenov M, Krasnov G. 2019. Indigenous endomycorrhizal fungi at salak (Salacca zalacca) plantations in Bali, Indonesia and their colonization of the roots. Biodiversitas 20: 2410-2416. Cultivation of snake fruit, commonly known as salak usually done organically on dry land with limited fertilizer in Bali. This research aimed to observe and to identify the indigenous endomycorrhizal fungi on salak roots. The exploration was carried out by collecting soil and root samples in salak producing areas in Bali, i.e. Bebandem and Selat of Karangasem Regency, Payangan of Gianyar, and Pupuan of Tabanan Regency. At each location, 9 random samples were taken, resulting in a total of 36 samples. Spore extraction was carried out using a wet filtration technique followed by centrifugation according to the method by Brunndrett et al. (2009). Morphological identification was carried out at the genus and species level using the Manual for Identification of Mycorrhiza Fungi for identifying Vesicular-Arbuscular-Mycorrhiza (VAM) fungi (Schenk and Perez, 1990), while molecular identification was carried out according to Tedersoo et al. (2014). The percentage of root infections was carried out using the coloring method with trypan blue. The results showed there were only two genera of endomycorrhizae (Glomus and Entrophospora) identified at the locations of study sites. The results also showed that samples from Bebandem and Selat regions had 3 Glomus species, Payangan had 3 Glomus species and 1 Entrophospora species, while in Pupuan had only 2 Glomus species. Identification results based on morphological characters showed that all species in the genus Glomus consisted of 3 species, namely Glomus sp-1, Glomus sp-2, and Glomus sp-3, while one species in the genus Entrophospora was Entrophospora sp. Genetic identification results based on the nucleotide arrangement showed that Glomus sp-1 concluded as Glomus cubence, Glomus sp-2 concluded as Glomus custos, and Glomus sp-3 concluded as Glomus indicum, while Entrophospora species concluded as Entrophospora_sp_SH197095.06FU. The average of root colonization/ infection was very high, reaching 93.33% in Bebandem and Selat, 95.00% in Pupuan, and 100% in Payangan. The very high root infection rates indicated that the indigenous endomycorrhiza found in these areas was very adaptive in salak plantation, so there is an opportunity to be developed as biofertilizers.